Median rhomboid glossitis as a sign of undiagnosed diabetes mellitus - a case report - Sulistyani, Erna; Triwahyuni, Iin Eliana; Astuti, Pudji; Swandari, Rindang (Faculty of Dentistry, Universitas Islam Sultan Agung, 2023)
Background: Median Rhomboid Glossitis (MRG) is included in the group of nodular-plaque-like candidiasis, a subtype of chronic hyperplastic candidiasis. A lot of literature suggests that MRG is a manifestation of Diabetes Mellitus (DM), but the association between DM and MRG is unclear until now. This article reports an MRG found in an undiagnosed diabetes mellitus patient. Case: In October 2019, A 71-year-old man came to RSGM Universitas Jember to fix his loose denture. In the oral examination, we found a well-bordering, atrophic oval area surrounded by thick- soft white plaque. In his leg, we found itchy papule, ulcer, and crust multiple lesions. The microscopic examination of the white plaque swab showed that the spore and hyphae were found to fill all fields of view. The direct sugar blood level test showed that the sugar blood level was 390 mg/dL. We diagnosed the patient as having an MRG associated with suspected DM. Case Management: The patient was given miconazole oral gel and recommended to use it after cleaning the tongue three times a day. For diabetes management, the patient was referred to the Unit Medical Center University of Jember. The patient was diagnosed with diabetes mellitus and given oral-antidiabetics. After two weeks, the atrophic area had improved, and the white plaque had disappeared. Conclusion: General practitioners must be aware if they find the MRG in their patients caused a probability of underlying undiagnosed systemic disease, particularly diabetes mellitus on them.